Dwindling the Effect of Heavy Metals for Shallow water in Almadain Region - Abass, Mohammed Fadhel; Ahmed, Salam Hatif (Al-Adab Journal, 2020)
It was found that the iron and manganese element at the site (o) represents the Diyala River before meeting at the Tigris River. Their language values ​​during November were 6.51 and 5.12 for iron and manganese respectively . During February, it reached 8.36 and 6.203, respectively. The site turns out to be invalid for the purpose of planting winter crops because it negatively affects them. As for the other factors, they are within the limited accepted barriers that agree with the factor related to food organisation and International nutrition.